Defining nocturnal polyuria in women. Issue 1 (21st October 2020) - Baines, Georgina; Da Silva, Ana Sofia; Cardozo, Linda; Bach, Fiona; Parsons, Matthew; Robinson, Dudley; Toozs‐Hobson, Philip
Abstract: Aims: Nocturnal polyuria (NP) is defined by the International Continence Society (ICS) as "excessive production of urine during the main sleep period" and is one of the main causes of nocturia. The ICS recognized that "excessive" is not clearly defined and that this needs to be highlighted in both clinical and research settings. The aim of this study was to identify different definitions of NP and apply them to a population of women attending the Urogynaecology clinic. Methods: This was a retrospective study of complete bladder diaries collected from women attending a tertiary Urogynaecology Unit. Six different definitions were identified and were divided into "absolute, " "relative, " and "functional definitions." Prevalence data were calculated and values generated for sensitivity, specificity, positive and negative predictive values when related to women voiding ≥ 2 times per night. Results: Complete bladder diaries were obtained from 1398 women, over 6 years, with a mean age of 57 years. Prevalence varied across the definitions from 21.5% (absolute definition) to 77% (relative definition). Sensitivity ranged from 43% (absolute) to 87% (relative). The definitions that showed the highest combined sensitivity and specificity were the functional definitions. Conclusion: From this study it is clear that more work needs to be done to arrive at a consensus for defining NP to enable accurate diagnosis and development of treatment pathways. We propose that a relative definition may provide a more clinically relevant method of defining NP.